ANALISIS FRAMING PEMBERITAAN TINDAKAN PENGANIAYAAN OLEH ANAK PEJABAT DIREKTORAT PAJAK DALAM KOMPAS.COM DAN LIPUTAN6.COM - Reni Astika Gea; Agustinus Rustanta (Universitas Tarakanita, 2024)
This study examines the phenomenon of persecution that is happening in Indonesia. The purpose of this study is to see the framing carried out by online sites Kompas.com and Liputan6.com in reporting on acts of persecution by children of Directorate General of Taxes Officials. This research is motivated by the tendency of different news angles from each of these media. This qualitative method of research uses Robert N. Entman's framing analysis model. This model has 4 elements as a framing tool, namely define problem, diagnose causes, make moral judgement, and treatment recommendation. The theory used in this study is the theory of social reality construction introduced by Peter L. Berger and Thomas Luckman. The results of the study show that Kompas.com and Liputan6.com choose the same issue to publish to readers. However, the two have different points of view in reporting on acts of persecution. Kompas.com tend to package issues in detail and carefully. Meanwhile, Liputan6.com packaged the issue briefly and emphasized more on the use of controversial titles to lead public opinion. It can be concluded that the two media have different viewpoints and ideologies in providing information to the public.